Software architecture : a case based approach - Varma, Vasudeva (Dorling Kindersley, 2009)
The book discusses the discipline of Software Architecture using real-world case studies and poses pertinent questions that arouse objective thinking. With the help of case studies and in-depth analyses, it delves into the core issues and challenges of software architecture.